Pengaruh Sistem Penataan Ruang Terhadap Minat Baca Siswa Di SMPN 1 Sungai Tarab - Cut - Afrina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The purpose of this study was to find out how the library spatial planning system at SMPN 1 Sungai Tarab works. The layout of the school library is the arrangement or arrangement of all school library facilities in the available space or building. Where by paying attention to the library spatial arrangement system in the school the writer was able to find out how much interest is in reading at SMPN 1 Sungai Tarab where interest in reading is a potential to read voluntarily.